2019
DOI: 10.1002/jcp.28562
|View full text |Cite
|
Sign up to set email alerts
|

Administration of dexamethasone disrupts endometrial receptivity by alteration of expression of miRNA 223, 200a, LIF, Muc1, SGK1, and ENaC via the ERK1/2‐mTOR pathway

Abstract: Successful implantation of embryos requires endometrial receptivity. Glucocorticoids are one of the factors influencing the implantation window. In this study, 40 female BALB/c mice were used to study the impacts of dexamethasone administration on endometrial receptivity markers during implantation window. The mice mated and were randomly divided into four groups: control (vehicle), dexamethasone (100 μg/kg, IP), PP242 (30 mg/kg, IP), and dexamethasone + PP242 (Dex + PP242). On the Day 4th and 5th of gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 68 publications
0
13
0
2
Order By: Relevance
“…miR-223-3p also suppresses the expression of leukemia inhibitory factor (LIF) during the implantation window in mouse uterus [46], a target that is essential for embryo implantation in both humans and mice [47,48]. A previous study confirms the upregulation of miR-223-3p in human endometrium with a compromised receptivity phenotype and its interaction with LIF [49]. In support, in our recent study we reveal that miR-223-3p is detected at low levels in the primary fertile human endometrial epithelial cells [50].…”
Section: Discussionmentioning
confidence: 91%
“…miR-223-3p also suppresses the expression of leukemia inhibitory factor (LIF) during the implantation window in mouse uterus [46], a target that is essential for embryo implantation in both humans and mice [47,48]. A previous study confirms the upregulation of miR-223-3p in human endometrium with a compromised receptivity phenotype and its interaction with LIF [49]. In support, in our recent study we reveal that miR-223-3p is detected at low levels in the primary fertile human endometrial epithelial cells [50].…”
Section: Discussionmentioning
confidence: 91%
“…However, glucocorticoids have recently been investigated as independent direct regulators of various uterine functions. For instance, Shariati et al found significantly decreased endometrial cell proliferation and a subsequent reduction in uterine receptivity during implantation in animals exposed to glucocorticoids by altering the expression of Muc1, SGK1, ENaC, miRNA 200a, and miRNA 223-3p via the ERK1/2-mTOR signaling pathway [ 50 ]. Similarly, Cooper et al observed a significant increase in the concentration of endometrial uterine NK cells in patients who had received synthetic glucocorticoid prednisolone [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial receptivity is a prerequisite to render the uterus suitable for embryo adhesion and to establish pregnancy in ruminants [18,19]. Although the molecular mechanism of regulating endometrial receptivity remains unclear, it is well-documented that altered gene expression in EECs during early pregnancy guarantees the success of embryo implantation [32]. Previous studies reported that exosomal proteins derived from day 17 pregnant ewes up-regulated BCL2L15 protein expression [10].…”
Section: Discussionmentioning
confidence: 99%